PERAN INSTAGRAM DALAM PENYAMPAIAN INFORMASI MAKEUP DI KALANGAN MAHASISWA TATA KECANTIKAN - Faradicka Husnul Khuluq; Maria Krisnawati (EDUTECH : Jurnal Inovasi Pendidikan Berbantuan Teknologi, 2026)
ABSTRACT The development of social media, especially Instagram, has influenced the delivery of information in various fields, including beauty education. Instagram is widely used by students as a source of references for makeup techniques, beauty trends, and product usage because it is visually oriented and easily accessible. The platform provides various types of content such as makeup tutorials, product reviews, and beauty trend information that attract users. However, studies specifically examining the role of Instagram in delivering makeup information among beauty education students are still limited. In addition, not all information shared on Instagram can be fully understood because the platform often emphasizes visual aspects rather than detailed explanations. Therefore, this study aims to examine the role of Instagram in delivering makeup information among beauty education students. This study employed a quantitative descriptive approach involving 62 beauty education students from the 2022 cohort as respondents. Data were collected using a 4-point Likert scale questionnaire that had been tested for validity and reliability. The data were analyzed using mean scores and percentages. The findings showed that Instagram plays a positive role in delivering makeup information among beauty education students. The attractiveness of the content, usefulness of information, clarity of information, and ease of understanding were categorized as good to very good. Based on these findings, it can be concluded that Instagram functions not only as an entertainment platform but also as an effective medium for information and learning in the field of beauty. Nevertheless, improvements in the quality of information presentation are still needed to make the content clearer, more educational, and easier for users to understand. ABSTRAK Perkembangan media sosial, khususnya Instagram, telah memengaruhi penyampaian informasi di berbagai bidang, termasuk tata kecantikan. Instagram banyak digunakan mahasiswa sebagai sumber referensi makeup, tren kecantikan, dan penggunaan produk karena bersifat visual dan mudah diakses. Platform ini menyediakan konten seperti tutorial, ulasan produk, dan informasi tren yang menarik. Namun, kajian tentang peran Instagram dalam penyampaian informasi makeup di kalangan mahasiswa tata kecantikan masih terbatas. Selain itu, tidak semua informasi di Instagram mudah dipahami secara mendalam karena lebih menekankan aspek visual daripada penjelasan rinci. Oleh karena itu, penelitian ini bertujuan untuk mengetahui peran Instagram dalam penyampaian informasi makeup di kalangan mahasiswa tata kecantikan. Penelitian ini menggunakan pendekatan deskriptif kuantitatif dengan subjek penelitian 62 responden mahaiswa tata kecantikan angkatan 2022. Teknik pengumpulan data menggunakan kuesioner dengan skala Likert 4 poin yang telah diuji validitas dan reliabilitasnya. Analisis data dilakukan menggunakan nilai rata-rata (mean) dan persentase. Hasil penelitian menunjukkan bahwa Instagram memiliki peran yang baik dalam penyampaian informasi makeup di kalangan mahasiswa tata kecantikan. Temuan penelitian menunjukkan bahwa daya tarik konten, manfaat informasi, kejelasan informasi, dan kemudahan pemahaman berada pada kategori baik hingga sangat baik. Berdasarkan hasil tersebut, dapat disimpulkan bahwa Instagram tidak hanya berfungsi sebagai media hiburan, tetapi juga sebagai media informasi dan pembelajaran yang cukup efektif dalam bidang tata kecantikan. Namun demikian, masih diperlukan peningkatan dalam kualitas penyajian informasi agar lebih jelas, edukatif, dan mudah dipahami oleh pengguna.